Unifying time-to-build theory - Mauro Bambi (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
Several contributions have recently reconsidered the role of the time to build assumption in explaining some relevant stylized facts. In this paper, the similarities and differences which may emerge when the time to build structure of capital is introduced in a continuous or discrete time framework are studied and enlightened. The most striking difference lies in the dimensionality of the two frameworks, which is always finite in discrete but infinite in continuous time. Then, the deterministic version of the traditional time to build model developed by Kydland and Prescott is presented, and it is shown how the typical time to build model setup in continuous time can be obtained. Moreover, the richest dynamics in continuous time is investigated and, more importantly, it is shown that the predictions in terms of capital, output, and consumption behavior are not signicantly di®erent from its discrete version once the economy is calibrated properly.
Keywords: E00; E30; O40; 330; Discrete and continuous time; time-to-build; mixed functional differential equations; Bruttoinlandsprodukt; Zeitökonomie; Makroökonometrie; Theorie